2014
DOI: 10.1111/ipd.12101
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of dental erosion of a sports drink by nano‐sized hydroxyapatite in situ study

Abstract: The sports drink containing 0.25% nano-HA was effective in preventing dental erosion in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Thus, the knowledge about the possible damages that a type of beverage can cause seem to be essential to prevent irreversible injuries. Moreover, recent studies have also focused on additive compounds to prevent erosion 24 , or on the influence of external agents, such as toothpastes and its components, to recover the demineralized dental tissue 25 .…”
Section: Consumption Of Ed Among Young People Is High and Tendsmentioning
confidence: 99%
“…Thus, the knowledge about the possible damages that a type of beverage can cause seem to be essential to prevent irreversible injuries. Moreover, recent studies have also focused on additive compounds to prevent erosion 24 , or on the influence of external agents, such as toothpastes and its components, to recover the demineralized dental tissue 25 .…”
Section: Consumption Of Ed Among Young People Is High and Tendsmentioning
confidence: 99%
“…Preventive and therapeutic strategies for dental erosion have been widely proposed in the dental literature and are based mostly on data from in vitro and in situ studies [Bellamy et al, 2014;Algarni et al, 2015;Min et al, 2015b;Scaramucci et al, 2015]. These well-controlled experimental models allow the test of very specific research questions, using analytical methods.…”
mentioning
confidence: 99%
“…As for caries treatment, Hannig M said that Analysis of in vitro data indicates that apatite nanoparticles might be effective in reversing lesion progression in the outer but not in the deeper part of early caries lesions [8]. Liu Y, et al, J Nanotechnol Nanomed Nanobiotechnol 2017, 4: 011 DOI: 10.24966/NTMB-2044 HSOA Journal of Nanotechnology: Nanomedicine & Nanobiotechnology…”
Section: The Nanomaterials Commonly Used In Dentistrymentioning
confidence: 99%
“…Nagano F found that Colloidal Platinum Nanoparticles (CPN) can prolong the durability of bonds, creating a higher conversion at the interface [10]. As a new dental restorative material, new nano-hydroxyapatite composite resin has superior bonding ability and can be used in clinical therapy [7].It is interesting that a sports drink containing 0.25% nano HA was effective in preventing dental erosion in situ [8]. Adding some nanomaterials into the common dental cure binder can cure dentine hypersensitivity by blocking off dentin tubules [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation